(untitled) (Research, Society and Development, 2025)
Objective: To map in the literature studies that address quality indicators for the managerial processes of clinical simulation centers/laboratories. Methods: A scoping review protocol conducted according to the Joanna Briggs Institute (JBI) guidelines and following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). The search will be carried out in databases such as Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Latin American and Caribbean Health Sciences Literature (LILACS), and SCOPUS, in addition to Google Scholar as a source of gray literature, including articles published from 1990 onwards. There will be no restrictions regarding language, or study design. Article selection will follow a screening process conducted by two independent reviewers using Rayyan® software, with conflict resolution by a third reviewer. Extracted data will be organized and presented descriptively through tables, graphs, and flowcharts, following JBI guidelines. This review is expected to map the existing literature on quality indicators for the managerial processes of clinical simulation centers/laboratories, supporting the development and validation of these indicators.